TORSIONAL VIBRATION ANALYSIS OF RV REDUCER BASED ON VARIATIONAL MODE DECOMPOSITION - ZHANG Jieting; YU Dong; LOU Junqiang; LUO Limin; GONG Linhuan; LI Guoping (Jixie qiangdu)
To investigate the vibration performance of RV reducers and analyze the fault identification, the torsional vibration test bench for RV reducers was built.Based on the mechanical structure and transmission principles of RV reducers, the vibration frequencies under different operating conditions were calculated.The vibration signal of RV reducers of superior and inferior products was collected, and the acceleration signal of the torsional vibration under different speeds and swerves was collected.The torsional vibration signals were decomposed using the variational mode decomposition (VMD) to obtain the intrinsic mode function (IMF).The results demonstrate a high correlation between the extracted IMF features obtained through VMD and the vibration frequencies observed during the operation of RV reducers.Furthermore, by comparing the spectrum of IMF, the reasons behind the abnormal vibration in inferior RV reducers were identified.Ultimately, it is determined that the abnormal vibration in inferior RV reducers were caused by the excitation from the interaction between the auto rotation of the planetary gear and the crankshaft or the revolution of the cycloid gear.This study provides valuable insights for enterprises aiming to improve the transmission accuracy and product quality of RV reducers.